2006
DOI: 10.1111/j.1939-165x.2006.tb00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet aggregation studies in acute experimental canine ehrlichiosis

Abstract: The tendency of dogs infected with E canis to bleed may be related not only to thrombocytopenia but also to platelet dysfunction associated with the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…Conditions like hepatomegaly and splenomegaly [2] as well as lymphadenomegaly [22] were detected mostly in acute conditions. Bleeding tendencies may be attributed to a combination of mild thrombocytopenia and vasculitis [28]. Out of the 70 positive cases, six dogs succumbed to death (four pure CME, one with additional infection of B. gibsoni and other with T. evansi), 50 % of which were German Shepherd echoing the more severe form with poor prognosis in this breed [2].…”
Section: Clinico-incidental Studymentioning
confidence: 99%
“…Conditions like hepatomegaly and splenomegaly [2] as well as lymphadenomegaly [22] were detected mostly in acute conditions. Bleeding tendencies may be attributed to a combination of mild thrombocytopenia and vasculitis [28]. Out of the 70 positive cases, six dogs succumbed to death (four pure CME, one with additional infection of B. gibsoni and other with T. evansi), 50 % of which were German Shepherd echoing the more severe form with poor prognosis in this breed [2].…”
Section: Clinico-incidental Studymentioning
confidence: 99%
“…Thus, it has been suggested that bleeding in ehrlichiosis is of multifactorial origin 25. In consequence, there are tangible explanations and support as to why our patient developed cerebral haemorrhage without thrombocytopaenia.…”
Section: Discussionmentioning
confidence: 56%
“…Estudos anteriores apontam apenas alterações na função plaquetária de cães com erliquiose (Gaunt et al 1990, Harrus et al 1996, Brandão et al 2006, Cortese et al 2006, sendo este o primeiro relato de alterações hemostáticas em cães com erliquiose sem envolvimento imuno-mediado.…”
Section: Discussionunclassified